Egyptian students' guardians knowledge, attitude and predictors of negative attitude of epilepsy in Assiut city - Ghaydaa A. Shehata; Dalia G. Mahran (Springer, 2019)
Background: Epilepsy is very prevalent in Egypt, approaching 6.98 per 1000 population. This study was designed to assess the knowledge and attitudes towards epilepsy among guardians of Egyptian high school students. Methods: A cross-sectional study was made among guardians (parents/guardians) of high school students in Assiut city, Egypt. A 15-item questionnaire was self-administered by 1257 students' guardians who were randomly selected. Results: All recruited parents/guardians of high school students had heard about epilepsy. Families with a patient with epilepsy (PWE) had significantly better information about epilepsy and its aetiology than other families. The predictors of negative attitudes towards PWE were: age group ranging from 40 to 49 years, no work, skilled work, male sex and incorrect knowledge. Conclusion: Having a patient with epilepsy is a predictor to having greater knowledge and a better attitude towards epilepsy. However, people still have a concept that PWE are stigmatized and are different from others. Raising awareness about epilepsy and its aetiology will increase the knowledge and improve the attitudes towards PWE.